The Tutor Perceptions of Community Service in ESA Hamzanwadi Organization - Saifudin, M. Saddam Kiramuddin Al-Wathani; Agustina, Yulia; Arfah, Hajriana; Husnu, Muhamnad (Unram Journal of Community Service, 2025)
This study explores the perceptions of tutors from the English Student Association (ESA) at Hamzanwadi University regarding their participation in a community service program held from 2022 to 2024. Using a qualitative descriptive approach, data were collected through questionnaires and semi-structured interviews with purposively selected participants. The study findings indicate that the community service program has had a significant impact on the academic, social, and personal development of prospective tutors. Most tutors considered this activity a valuable experiential learning platform that improved their communication, teaching skills, self-confidence, and leadership. This analysis is supported by experiential learning theory (Kolb, 1984), the concept of service-based learning (Dewey & Freire), and the principles of assistive therapy (Riessman, 1965), which collectively demonstrate that community service not only benefits the community but also fosters meaningful personal growth among participating students. This study recommends continued support and institutionalization of community service programs as part of professional and character development in higher education.